Mutual antagonism between the Ebola virus VP35 protein and the RIG-I activator PACT determines infection outcome - Luthra, Priya; Ramanan, Parameshwaran; Mire, Chad E; Weisend, Carla; Tsuda, Yoshimi; Yen, Benjamin; Liu, Gai; Leung, Daisy W; Geisbert, Thomas W; Ebihara, Hideki; Amarasinghe, Gaya K; Basler, Christopher F (Cell host & microbe, 2013)
The cytoplasmic pattern recognition receptor RIG-I is activated by viral RNA and induces type I IFN responses to control viral replication. The cellular dsRNA binding protein PACT can also activate RIG-I. To counteract innate antiviral responses, some viruses, including Ebola virus (EBOV), encode proteins that antagonize RIG-I signaling. Here, we show that EBOV VP35 inhibits PACT-induced RIG-I ATPase activity in a dose-dependent manner. The interaction of PACT with RIG-I is disrupted by wild-type VP35, but not by VP35 mutants that are unable to bind PACT. In addition, PACT-VP35 interaction impairs the association between VP35 and the viral polymerase, thereby diminishing viral RNA synthesis and modulating EBOV replication. PACT-deficient cells are defective in IFN induction and are insensitive to VP35 function. These data support a model in which the VP35-PACT interaction is mutually antagonistic and plays a fundamental role in determining the outcome of EBOV infection.